EquivProgram Equivalence
Set Warnings "-notation-overridden,-parsing,-deprecated-hint-without-locality".
From PLF Require Import Maps.
From Coq Require Import Bool.Bool.
From Coq Require Import Arith.Arith.
From Coq Require Import Init.Nat.
From Coq Require Import Arith.PeanoNat. Import Nat.
From Coq Require Import Arith.EqNat.
From Coq Require Import Lia.
From Coq Require Import Lists.List. Import ListNotations.
From Coq Require Import Logic.FunctionalExtensionality.
From PLF Require Export Imp.
From PLF Require Import Maps.
From Coq Require Import Bool.Bool.
From Coq Require Import Arith.Arith.
From Coq Require Import Init.Nat.
From Coq Require Import Arith.PeanoNat. Import Nat.
From Coq Require Import Arith.EqNat.
From Coq Require Import Lia.
From Coq Require Import Lists.List. Import ListNotations.
From Coq Require Import Logic.FunctionalExtensionality.
From PLF Require Export Imp.
Before You Get Started:
- Create a fresh directory for this volume. (Do not try to mix the
files from this volume with files from Logical Foundations in
the same directory: the result will not make you happy.) You
can either start with an empty directory and populate it with
the files listed below, or else download the whole PLF zip file
and unzip it.
- The new directory should contain at least the following files:
- Imp.v (make sure it is the one from the PLF distribution, not the one from LF: they are slightly different);
- Maps.v (ditto)
- Equiv.v (this file)
- _CoqProject, containing the following line:
-Q . PLF
- If you see errors like this...
Compiled library PLF.Maps (in file
/Users/.../plf/Maps.vo) makes inconsistent assumptions
over library Coq.Init.Logic ... it may mean something went wrong with the above steps. Doing "make clean" (or manually removing everything except .v and _CoqProject files) may help. - If you are using VSCode with the VSCoq extension, you'll then want to open a new window in VSCode, click Open Folder > plf, and run make. If you get an error like "Cannot find a physical path..." error, it may be because you didn't open plf directly (you instead opened a folder containing both lf and plf, for example).
Advice for Working on Exercises:
- Most of the Coq proofs we ask you to do in this chapter are
similar to proofs that we've provided. Before starting to work
on exercises, take the time to work through our proofs (both
informally and in Coq) and make sure you understand them in
detail. This will save you a lot of time.
- The Coq proofs we're doing now are sufficiently complicated that
it is more or less impossible to complete them by random
experimentation or following your nose. You need to start with
an idea about why the property is true and how the proof is
going to go. The best way to do this is to write out at least a
sketch of an informal proof on paper -- one that intuitively
convinces you of the truth of the theorem -- before starting to
work on the formal one. Alternately, grab a friend and try to
convince them that the theorem is true; then try to formalize
your explanation.
- Use automation to save work! The proofs in this chapter can get pretty long if you try to write out all the cases explicitly.
Behavioral Equivalence
Definitions
Definition aequiv (a1 a2 : aexp) : Prop :=
∀ (st : state),
aeval st a1 = aeval st a2.
Definition bequiv (b1 b2 : bexp) : Prop :=
∀ (st : state),
beval st b1 = beval st b2.
∀ (st : state),
aeval st a1 = aeval st a2.
Definition bequiv (b1 b2 : bexp) : Prop :=
∀ (st : state),
beval st b1 = beval st b2.
Here are some simple examples of equivalences of arithmetic
and boolean expressions.
Theorem aequiv_example:
aequiv
<{ X - X }>
<{ 0 }>.
Theorem bequiv_example:
bequiv
<{ X - X = 0 }>
<{ true }>.
aequiv
<{ X - X }>
<{ 0 }>.
Proof.
intros st. simpl. lia.
Qed.
intros st. simpl. lia.
Qed.
Theorem bequiv_example:
bequiv
<{ X - X = 0 }>
<{ true }>.
For commands, the situation is a little more subtle. We
can't simply say "two commands are behaviorally equivalent if they
evaluate to the same ending state whenever they are started in the
same initial state," because some commands, when run in some
starting states, don't terminate in any final state at all!
What we need instead is this: two commands are behaviorally
equivalent if, for any given starting state, they either (1) both
diverge or (2) both terminate in the same final state. A compact
way to express this is "if the first one terminates in a
particular state then so does the second, and vice versa."
Definition cequiv (c1 c2 : com) : Prop :=
∀ (st st' : state),
(st =[ c1 ]=> st') ↔ (st =[ c2 ]=> st').
Definition refines (c1 c2 : com) : Prop :=
∀ (st st' : state),
(st =[ c1 ]=> st') → (st =[ c2 ]=> st').
∀ (st st' : state),
(st =[ c1 ]=> st') ↔ (st =[ c2 ]=> st').
Definition refines (c1 c2 : com) : Prop :=
∀ (st st' : state),
(st =[ c1 ]=> st') → (st =[ c2 ]=> st').
Simple Examples
Theorem skip_left : ∀ c,
cequiv
<{ skip; c }>
c.
Proof.
(* WORKED IN CLASS *)
intros c st st'.
split; intros H.
- (* -> *)
inversion H. subst.
inversion H2. subst.
assumption.
- (* <- *)
apply E_Seq with st.
apply E_Skip.
assumption.
Qed.
cequiv
<{ skip; c }>
c.
Proof.
(* WORKED IN CLASS *)
intros c st st'.
split; intros H.
- (* -> *)
inversion H. subst.
inversion H2. subst.
assumption.
- (* <- *)
apply E_Seq with st.
apply E_Skip.
assumption.
Qed.
Exercise: 2 stars, standard (skip_right)
Prove that adding a skip after a command results in an equivalent program
Theorem if_true_simple : ∀ c1 c2,
cequiv
<{ if true then c1 else c2 end }>
c1.
cequiv
<{ if true then c1 else c2 end }>
c1.
Proof.
intros c1 c2.
split; intros H.
- (* -> *)
inversion H; subst. assumption. discriminate.
- (* <- *)
apply E_IfTrue. reflexivity. assumption. Qed.
intros c1 c2.
split; intros H.
- (* -> *)
inversion H; subst. assumption. discriminate.
- (* <- *)
apply E_IfTrue. reflexivity. assumption. Qed.
Of course, no (human) programmer would write a conditional whose
condition is literally true. But they might write one whose
condition is equivalent to true: Theorem: If b is equivalent to true, then if b then c1
else c2 end is equivalent to c1.
Proof:
Here is the formal version of this proof:
- (→) We must show, for all st and st', that if st =[
if b then c1 else c2 end ]=> st' then st =[ c1 ]=> st'.
- Suppose the final rule in the derivation of st =[ if b
then c1 else c2 end ]=> st' was E_IfTrue. We then have,
by the premises of E_IfTrue, that st =[ c1 ]=> st'.
This is exactly what we set out to prove.
- On the other hand, suppose the final rule in the derivation
of st =[ if b then c1 else c2 end ]=> st' was E_IfFalse.
We then know that beval st b = false and st =[ c2 ]=> st'.
- Suppose the final rule in the derivation of st =[ if b
then c1 else c2 end ]=> st' was E_IfTrue. We then have,
by the premises of E_IfTrue, that st =[ c1 ]=> st'.
This is exactly what we set out to prove.
- (<-) We must show, for all st and st', that if
st =[ c1 ]=> st' then
st =[ if b then c1 else c2 end ]=> st'.
Theorem if_true: ∀ b c1 c2,
bequiv b <{true}> →
cequiv
<{ if b then c1 else c2 end }>
c1.
bequiv b <{true}> →
cequiv
<{ if b then c1 else c2 end }>
c1.
Proof.
intros b c1 c2 Hb.
split; intros H.
- (* -> *)
inversion H. subst.
+ (* b evaluates to true *)
assumption.
+ (* b evaluates to false (contradiction) *)
unfold bequiv in Hb. simpl in Hb.
rewrite Hb in H5.
discriminate.
- (* <- *)
apply E_IfTrue; try assumption.
unfold bequiv in Hb. simpl in Hb.
apply Hb. Qed.
intros b c1 c2 Hb.
split; intros H.
- (* -> *)
inversion H. subst.
+ (* b evaluates to true *)
assumption.
+ (* b evaluates to false (contradiction) *)
unfold bequiv in Hb. simpl in Hb.
rewrite Hb in H5.
discriminate.
- (* <- *)
apply E_IfTrue; try assumption.
unfold bequiv in Hb. simpl in Hb.
apply Hb. Qed.
Theorem if_false : ∀ b c1 c2,
bequiv b <{false}> →
cequiv
<{ if b then c1 else c2 end }>
c2.
Proof.
(* FILL IN HERE *) Admitted.
☐
bequiv b <{false}> →
cequiv
<{ if b then c1 else c2 end }>
c2.
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 3 stars, standard (swap_if_branches)
Show that we can swap the branches of an if if we also negate its condition.
Theorem swap_if_branches : ∀ b c1 c2,
cequiv
<{ if b then c1 else c2 end }>
<{ if ¬ b then c2 else c1 end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
cequiv
<{ if b then c1 else c2 end }>
<{ if ¬ b then c2 else c1 end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Theorem while_false : ∀ b c,
bequiv b <{false}> →
cequiv
<{ while b do c end }>
<{ skip }>.
bequiv b <{false}> →
cequiv
<{ while b do c end }>
<{ skip }>.
Proof.
intros b c Hb. split; intros H.
- (* -> *)
inversion H. subst.
+ (* E_WhileFalse *)
apply E_Skip.
+ (* E_WhileTrue *)
rewrite Hb in H2. discriminate.
- (* <- *)
inversion H. subst.
apply E_WhileFalse.
apply Hb. Qed.
intros b c Hb. split; intros H.
- (* -> *)
inversion H. subst.
+ (* E_WhileFalse *)
apply E_Skip.
+ (* E_WhileTrue *)
rewrite Hb in H2. discriminate.
- (* <- *)
inversion H. subst.
apply E_WhileFalse.
apply Hb. Qed.
Exercise: 2 stars, advanced, optional (while_false_informal)
Write an informal proof of while_false.☐
- Suppose st =[ while b do c end ]=> st' is proved using rule
E_WhileFalse. Then by assumption beval st b = false. But
this contradicts the assumption that b is equivalent to
true.
- Suppose st =[ while b do c end ]=> st' is proved using rule
E_WhileTrue. We must have that:
Lemma while_true_nonterm : ∀ b c st st',
bequiv b <{true}> →
~( st =[ while b do c end ]=> st' ).
Proof.
(* WORKED IN CLASS *)
intros b c st st' Hb.
intros H.
remember <{ while b do c end }> as cw eqn:Heqcw.
induction H;
(* Most rules don't apply; we rule them out by inversion: *)
inversion Heqcw; subst; clear Heqcw.
(* The two interesting cases are the ones for while loops: *)
- (* E_WhileFalse *) (* contradictory -- b is always true! *)
unfold bequiv in Hb.
(* rewrite is able to instantiate the quantifier in st *)
rewrite Hb in H. discriminate.
- (* E_WhileTrue *) (* immediate from the IH *)
apply IHceval2. reflexivity. Qed.
bequiv b <{true}> →
~( st =[ while b do c end ]=> st' ).
Proof.
(* WORKED IN CLASS *)
intros b c st st' Hb.
intros H.
remember <{ while b do c end }> as cw eqn:Heqcw.
induction H;
(* Most rules don't apply; we rule them out by inversion: *)
inversion Heqcw; subst; clear Heqcw.
(* The two interesting cases are the ones for while loops: *)
- (* E_WhileFalse *) (* contradictory -- b is always true! *)
unfold bequiv in Hb.
(* rewrite is able to instantiate the quantifier in st *)
rewrite Hb in H. discriminate.
- (* E_WhileTrue *) (* immediate from the IH *)
apply IHceval2. reflexivity. Qed.
Exercise: 2 stars, standard, optional (while_true_nonterm_informal)
Explain what the lemma while_true_nonterm means in English.☐
Exercise: 2 stars, standard, especially useful (while_true)
Prove the following theorem. Hint: You'll want to use while_true_nonterm here.
Theorem while_true : ∀ b c,
bequiv b <{true}> →
cequiv
<{ while b do c end }>
<{ while true do skip end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
bequiv b <{true}> →
cequiv
<{ while b do c end }>
<{ while true do skip end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Theorem loop_unrolling : ∀ b c,
cequiv
<{ while b do c end }>
<{ if b then c ; while b do c end else skip end }>.
Proof.
(* WORKED IN CLASS *)
cequiv
<{ while b do c end }>
<{ if b then c ; while b do c end else skip end }>.
Proof.
(* WORKED IN CLASS *)
intros b c st st'.
split; intros Hce.
- (* -> *)
inversion Hce; subst.
+ (* loop doesn't run *)
apply E_IfFalse. assumption. apply E_Skip.
+ (* loop runs *)
apply E_IfTrue. assumption.
apply E_Seq with (st' := st'0). assumption. assumption.
- (* <- *)
inversion Hce; subst.
+ (* loop runs *)
inversion H5; subst.
apply E_WhileTrue with (st' := st'0).
assumption. assumption. assumption.
+ (* loop doesn't run *)
inversion H5; subst. apply E_WhileFalse. assumption. Qed.
split; intros Hce.
- (* -> *)
inversion Hce; subst.
+ (* loop doesn't run *)
apply E_IfFalse. assumption. apply E_Skip.
+ (* loop runs *)
apply E_IfTrue. assumption.
apply E_Seq with (st' := st'0). assumption. assumption.
- (* <- *)
inversion Hce; subst.
+ (* loop runs *)
inversion H5; subst.
apply E_WhileTrue with (st' := st'0).
assumption. assumption. assumption.
+ (* loop doesn't run *)
inversion H5; subst. apply E_WhileFalse. assumption. Qed.
Theorem seq_assoc : ∀ c1 c2 c3,
cequiv <{(c1;c2);c3}> <{c1;(c2;c3)}>.
Proof.
(* FILL IN HERE *) Admitted.
☐
cequiv <{(c1;c2);c3}> <{c1;(c2;c3)}>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Theorem identity_assignment : ∀ x,
cequiv
<{ x := x }>
<{ skip }>.
Proof.
intros.
split; intro H; inversion H; subst; clear H.
- (* -> *)
rewrite t_update_same.
apply E_Skip.
- (* <- *)
assert (Hx : st' =[ x := x ]=> (x !-> st' x ; st')).
{ apply E_Asgn. reflexivity. }
rewrite t_update_same in Hx.
apply Hx.
Qed.
cequiv
<{ x := x }>
<{ skip }>.
Proof.
intros.
split; intro H; inversion H; subst; clear H.
- (* -> *)
rewrite t_update_same.
apply E_Skip.
- (* <- *)
assert (Hx : st' =[ x := x ]=> (x !-> st' x ; st')).
{ apply E_Asgn. reflexivity. }
rewrite t_update_same in Hx.
apply Hx.
Qed.
Theorem assign_aequiv : ∀ (X : string) (a : aexp),
aequiv <{ X }> a →
cequiv <{ skip }> <{ X := a }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
aequiv <{ X }> a →
cequiv <{ skip }> <{ X := a }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 2 stars, standard (equiv_classes)
[ [prog_a;prog_b;prog_c;prog_d;prog_e;prog_f;prog_g;prog_h] ;
[prog_i] ] Write down your answer below in the definition of equiv_classes.
Definition prog_a : com :=
<{ while ¬(X ≤ 0) do
X := X + 1
end }>.
Definition prog_b : com :=
<{ if (X = 0) then
X := X + 1;
Y := 1
else
Y := 0
end;
X := X - Y;
Y := 0 }>.
Definition prog_c : com :=
<{ skip }> .
Definition prog_d : com :=
<{ while X ≠ 0 do
X := (X × Y) + 1
end }>.
Definition prog_e : com :=
<{ Y := 0 }>.
Definition prog_f : com :=
<{ Y := X + 1;
while X ≠ Y do
Y := X + 1
end }>.
Definition prog_g : com :=
<{ while true do
skip
end }>.
Definition prog_h : com :=
<{ while X ≠ X do
X := X + 1
end }>.
Definition prog_i : com :=
<{ while X ≠ Y do
X := Y + 1
end }>.
Definition equiv_classes : list (list com)
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
(* Do not modify the following line: *)
Definition manual_grade_for_equiv_classes : option (nat×string) := None.
☐
<{ while ¬(X ≤ 0) do
X := X + 1
end }>.
Definition prog_b : com :=
<{ if (X = 0) then
X := X + 1;
Y := 1
else
Y := 0
end;
X := X - Y;
Y := 0 }>.
Definition prog_c : com :=
<{ skip }> .
Definition prog_d : com :=
<{ while X ≠ 0 do
X := (X × Y) + 1
end }>.
Definition prog_e : com :=
<{ Y := 0 }>.
Definition prog_f : com :=
<{ Y := X + 1;
while X ≠ Y do
Y := X + 1
end }>.
Definition prog_g : com :=
<{ while true do
skip
end }>.
Definition prog_h : com :=
<{ while X ≠ X do
X := X + 1
end }>.
Definition prog_i : com :=
<{ while X ≠ Y do
X := Y + 1
end }>.
Definition equiv_classes : list (list com)
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
(* Do not modify the following line: *)
Definition manual_grade_for_equiv_classes : option (nat×string) := None.
☐
Properties of Behavioral Equivalence
Behavioral Equivalence Is an Equivalence
Lemma refl_aequiv : ∀ (a : aexp),
aequiv a a.
Lemma sym_aequiv : ∀ (a1 a2 : aexp),
aequiv a1 a2 → aequiv a2 a1.
Lemma trans_aequiv : ∀ (a1 a2 a3 : aexp),
aequiv a1 a2 → aequiv a2 a3 → aequiv a1 a3.
Lemma refl_bequiv : ∀ (b : bexp),
bequiv b b.
Lemma sym_bequiv : ∀ (b1 b2 : bexp),
bequiv b1 b2 → bequiv b2 b1.
Lemma trans_bequiv : ∀ (b1 b2 b3 : bexp),
bequiv b1 b2 → bequiv b2 b3 → bequiv b1 b3.
Lemma refl_cequiv : ∀ (c : com),
cequiv c c.
Lemma sym_cequiv : ∀ (c1 c2 : com),
cequiv c1 c2 → cequiv c2 c1.
Lemma trans_cequiv : ∀ (c1 c2 c3 : com),
cequiv c1 c2 → cequiv c2 c3 → cequiv c1 c3.
aequiv a a.
Proof.
intros a st. reflexivity. Qed.
intros a st. reflexivity. Qed.
Lemma sym_aequiv : ∀ (a1 a2 : aexp),
aequiv a1 a2 → aequiv a2 a1.
Proof.
intros a1 a2 H. intros st. symmetry. apply H. Qed.
intros a1 a2 H. intros st. symmetry. apply H. Qed.
Lemma trans_aequiv : ∀ (a1 a2 a3 : aexp),
aequiv a1 a2 → aequiv a2 a3 → aequiv a1 a3.
Proof.
unfold aequiv. intros a1 a2 a3 H12 H23 st.
rewrite (H12 st). rewrite (H23 st). reflexivity. Qed.
unfold aequiv. intros a1 a2 a3 H12 H23 st.
rewrite (H12 st). rewrite (H23 st). reflexivity. Qed.
Lemma refl_bequiv : ∀ (b : bexp),
bequiv b b.
Lemma sym_bequiv : ∀ (b1 b2 : bexp),
bequiv b1 b2 → bequiv b2 b1.
Lemma trans_bequiv : ∀ (b1 b2 b3 : bexp),
bequiv b1 b2 → bequiv b2 b3 → bequiv b1 b3.
Proof.
unfold bequiv. intros b1 b2 b3 H12 H23 st.
rewrite (H12 st). rewrite (H23 st). reflexivity. Qed.
unfold bequiv. intros b1 b2 b3 H12 H23 st.
rewrite (H12 st). rewrite (H23 st). reflexivity. Qed.
Lemma refl_cequiv : ∀ (c : com),
cequiv c c.
Lemma sym_cequiv : ∀ (c1 c2 : com),
cequiv c1 c2 → cequiv c2 c1.
Lemma trans_cequiv : ∀ (c1 c2 c3 : com),
cequiv c1 c2 → cequiv c2 c3 → cequiv c1 c3.
Behavioral Equivalence Is a Congruence
aequiv a a' | |
cequiv (x := a) (x := a') |
cequiv c1 c1' | |
cequiv c2 c2' | |
cequiv (c1;c2) (c1';c2') |
Theorem CAsgn_congruence : ∀ x a a',
aequiv a a' →
cequiv <{x := a}> <{x := a'}>.
aequiv a a' →
cequiv <{x := a}> <{x := a'}>.
Proof.
intros x a a' Heqv st st'.
split; intros Hceval.
- (* -> *)
inversion Hceval. subst. apply E_Asgn.
rewrite Heqv. reflexivity.
- (* <- *)
inversion Hceval. subst. apply E_Asgn.
rewrite Heqv. reflexivity. Qed.
intros x a a' Heqv st st'.
split; intros Hceval.
- (* -> *)
inversion Hceval. subst. apply E_Asgn.
rewrite Heqv. reflexivity.
- (* <- *)
inversion Hceval. subst. apply E_Asgn.
rewrite Heqv. reflexivity. Qed.
The congruence property for loops is a little more interesting,
since it requires induction.
Theorem: Equivalence is a congruence for while -- that is, if
b is equivalent to b' and c is equivalent to c', then
while b do c end is equivalent to while b' do c' end.
Proof: Suppose b is equivalent to b' and c is
equivalent to c'. We must show, for every st and st', that
st =[ while b do c end ]=> st' iff st =[ while b' do c'
end ]=> st'. We consider the two directions separately.
- (→) We show that st =[ while b do c end ]=> st' implies
st =[ while b' do c' end ]=> st', by induction on a
derivation of st =[ while b do c end ]=> st'. The only
nontrivial cases are when the final rule in the derivation is
E_WhileFalse or E_WhileTrue.
- E_WhileFalse: In this case, the form of the rule gives us
beval st b = false and st = st'. But then, since
b and b' are equivalent, we have beval st b' =
false, and E_WhileFalse applies, giving us
st =[ while b' do c' end ]=> st', as required.
- E_WhileTrue: The form of the rule now gives us beval st
b = true, with st =[ c ]=> st'0 and st'0 =[ while
b do c end ]=> st' for some state st'0, with the
induction hypothesis st'0 =[ while b' do c' end ]=>
st'.
- E_WhileFalse: In this case, the form of the rule gives us
beval st b = false and st = st'. But then, since
b and b' are equivalent, we have beval st b' =
false, and E_WhileFalse applies, giving us
st =[ while b' do c' end ]=> st', as required.
- (<-) Similar. ☐
Theorem CWhile_congruence : ∀ b b' c c',
bequiv b b' → cequiv c c' →
cequiv <{ while b do c end }> <{ while b' do c' end }>.
Proof.
(* WORKED IN CLASS *)
(* We will prove one direction in an "assert"
in order to reuse it for the converse. *)
assert (A: ∀ (b b' : bexp) (c c' : com) (st st' : state),
bequiv b b' → cequiv c c' →
st =[ while b do c end ]=> st' →
st =[ while b' do c' end ]=> st').
{ unfold bequiv,cequiv.
intros b b' c c' st st' Hbe Hc1e Hce.
remember <{ while b do c end }> as cwhile
eqn:Heqcwhile.
induction Hce; inversion Heqcwhile; subst.
+ (* E_WhileFalse *)
apply E_WhileFalse. rewrite <- Hbe. apply H.
+ (* E_WhileTrue *)
apply E_WhileTrue with (st' := st').
× (* show loop runs *) rewrite <- Hbe. apply H.
× (* body execution *)
apply (Hc1e st st'). apply Hce1.
× (* subsequent loop execution *)
apply IHHce2. reflexivity. }
intros. split.
- apply A; assumption.
- apply A.
+ apply sym_bequiv. assumption.
+ apply sym_cequiv. assumption.
Qed.
bequiv b b' → cequiv c c' →
cequiv <{ while b do c end }> <{ while b' do c' end }>.
Proof.
(* WORKED IN CLASS *)
(* We will prove one direction in an "assert"
in order to reuse it for the converse. *)
assert (A: ∀ (b b' : bexp) (c c' : com) (st st' : state),
bequiv b b' → cequiv c c' →
st =[ while b do c end ]=> st' →
st =[ while b' do c' end ]=> st').
{ unfold bequiv,cequiv.
intros b b' c c' st st' Hbe Hc1e Hce.
remember <{ while b do c end }> as cwhile
eqn:Heqcwhile.
induction Hce; inversion Heqcwhile; subst.
+ (* E_WhileFalse *)
apply E_WhileFalse. rewrite <- Hbe. apply H.
+ (* E_WhileTrue *)
apply E_WhileTrue with (st' := st').
× (* show loop runs *) rewrite <- Hbe. apply H.
× (* body execution *)
apply (Hc1e st st'). apply Hce1.
× (* subsequent loop execution *)
apply IHHce2. reflexivity. }
intros. split.
- apply A; assumption.
- apply A.
+ apply sym_bequiv. assumption.
+ apply sym_cequiv. assumption.
Qed.
Theorem CSeq_congruence : ∀ c1 c1' c2 c2',
cequiv c1 c1' → cequiv c2 c2' →
cequiv <{ c1;c2 }> <{ c1';c2' }>.
cequiv c1 c1' → cequiv c2 c2' →
cequiv <{ c1;c2 }> <{ c1';c2' }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
(* FILL IN HERE *) Admitted.
☐
Theorem CIf_congruence : ∀ b b' c1 c1' c2 c2',
bequiv b b' → cequiv c1 c1' → cequiv c2 c2' →
cequiv <{ if b then c1 else c2 end }>
<{ if b' then c1' else c2' end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
bequiv b b' → cequiv c1 c1' → cequiv c2 c2' →
cequiv <{ if b then c1 else c2 end }>
<{ if b' then c1' else c2' end }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Example congruence_example:
cequiv
(* Program 1: *)
<{ X := 0;
if (X = 0) then Y := 0
else Y := 42 end }>
(* Program 2: *)
<{ X := 0;
if (X = 0) then Y := X - X (* <--- Changed here *)
else Y := 42 end }>.
Proof.
apply CSeq_congruence.
- apply refl_cequiv.
- apply CIf_congruence.
+ apply refl_bequiv.
+ apply CAsgn_congruence. unfold aequiv. simpl.
symmetry. apply minus_diag.
+ apply refl_cequiv.
Qed.
cequiv
(* Program 1: *)
<{ X := 0;
if (X = 0) then Y := 0
else Y := 42 end }>
(* Program 2: *)
<{ X := 0;
if (X = 0) then Y := X - X (* <--- Changed here *)
else Y := 42 end }>.
Proof.
apply CSeq_congruence.
- apply refl_cequiv.
- apply CIf_congruence.
+ apply refl_bequiv.
+ apply CAsgn_congruence. unfold aequiv. simpl.
symmetry. apply minus_diag.
+ apply refl_cequiv.
Qed.
Exercise: 3 stars, advanced (not_congr)
We've shown that the cequiv relation is both an equivalence and a congruence on commands. Can you think of a relation on commands that is an equivalence but not a congruence? Write down the relation (formally), together with an informal sketch of a proof that it is an equivalence but not a congruence.
(* FILL IN HERE *)
(* Do not modify the following line: *)
Definition manual_grade_for_not_congr : option (nat×string) := None.
☐
(* Do not modify the following line: *)
Definition manual_grade_for_not_congr : option (nat×string) := None.
☐
Program Transformations
Definition atrans_sound (atrans : aexp → aexp) : Prop :=
∀ (a : aexp),
aequiv a (atrans a).
Definition btrans_sound (btrans : bexp → bexp) : Prop :=
∀ (b : bexp),
bequiv b (btrans b).
Definition ctrans_sound (ctrans : com → com) : Prop :=
∀ (c : com),
cequiv c (ctrans c).
∀ (a : aexp),
aequiv a (atrans a).
Definition btrans_sound (btrans : bexp → bexp) : Prop :=
∀ (b : bexp),
bequiv b (btrans b).
Definition ctrans_sound (ctrans : com → com) : Prop :=
∀ (c : com),
cequiv c (ctrans c).
The Constant-Folding Transformation
Fixpoint fold_constants_aexp (a : aexp) : aexp :=
match a with
| ANum n ⇒ ANum n
| AId x ⇒ AId x
| <{ a1 + a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 + n2)
| (a1', a2') ⇒ <{ a1' + a2' }>
end
| <{ a1 - a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 - n2)
| (a1', a2') ⇒ <{ a1' - a2' }>
end
| <{ a1 × a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 × n2)
| (a1', a2') ⇒ <{ a1' × a2' }>
end
end.
Example fold_aexp_ex1 :
fold_constants_aexp <{ (1 + 2) × X }>
= <{ 3 × X }>.
match a with
| ANum n ⇒ ANum n
| AId x ⇒ AId x
| <{ a1 + a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 + n2)
| (a1', a2') ⇒ <{ a1' + a2' }>
end
| <{ a1 - a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 - n2)
| (a1', a2') ⇒ <{ a1' - a2' }>
end
| <{ a1 × a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2)
with
| (ANum n1, ANum n2) ⇒ ANum (n1 × n2)
| (a1', a2') ⇒ <{ a1' × a2' }>
end
end.
Example fold_aexp_ex1 :
fold_constants_aexp <{ (1 + 2) × X }>
= <{ 3 × X }>.
Proof. reflexivity. Qed.
Note that this version of constant folding doesn't do other
"obvious" things like eliminating trivial additions (e.g.,
rewriting 0 + X to just X).: we are focusing attention on a
single optimization for the sake of simplicity.
It is not hard to incorporate other ways of simplifying
expressions -- the definitions and proofs just get longer. We'll
consider optimizations in the exercises.
Example fold_aexp_ex2 :
fold_constants_aexp <{ X - ((0 × 6) + Y) }> = <{ X - (0 + Y) }>.
fold_constants_aexp <{ X - ((0 × 6) + Y) }> = <{ X - (0 + Y) }>.
Proof. reflexivity. Qed.
Not only can we lift fold_constants_aexp to bexps (in the
BEq, BNeq, and BLe cases); we can also look for constant
boolean expressions and evaluate them in-place as well.
Fixpoint fold_constants_bexp (b : bexp) : bexp :=
match b with
| <{true}> ⇒ <{true}>
| <{false}> ⇒ <{false}>
| <{ a1 = a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if n1 =? n2 then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' = a2' }>
end
| <{ a1 ≠ a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if negb (n1 =? n2) then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' ≠ a2' }>
end
| <{ a1 ≤ a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if n1 <=? n2 then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' ≤ a2' }>
end
| <{ ¬ b1 }> ⇒
match (fold_constants_bexp b1) with
| <{true}> ⇒ <{false}>
| <{false}> ⇒ <{true}>
| b1' ⇒ <{ ¬ b1' }>
end
| <{ b1 && b2 }> ⇒
match (fold_constants_bexp b1,
fold_constants_bexp b2) with
| (<{true}>, <{true}>) ⇒ <{true}>
| (<{true}>, <{false}>) ⇒ <{false}>
| (<{false}>, <{true}>) ⇒ <{false}>
| (<{false}>, <{false}>) ⇒ <{false}>
| (b1', b2') ⇒ <{ b1' && b2' }>
end
end.
Example fold_bexp_ex1 :
fold_constants_bexp <{ true && ¬(false && true) }>
= <{ true }>.
Example fold_bexp_ex2 :
fold_constants_bexp <{ (X = Y) && (0 = (2 - (1 + 1))) }>
= <{ (X = Y) && true }>.
match b with
| <{true}> ⇒ <{true}>
| <{false}> ⇒ <{false}>
| <{ a1 = a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if n1 =? n2 then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' = a2' }>
end
| <{ a1 ≠ a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if negb (n1 =? n2) then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' ≠ a2' }>
end
| <{ a1 ≤ a2 }> ⇒
match (fold_constants_aexp a1,
fold_constants_aexp a2) with
| (ANum n1, ANum n2) ⇒
if n1 <=? n2 then <{true}> else <{false}>
| (a1', a2') ⇒
<{ a1' ≤ a2' }>
end
| <{ ¬ b1 }> ⇒
match (fold_constants_bexp b1) with
| <{true}> ⇒ <{false}>
| <{false}> ⇒ <{true}>
| b1' ⇒ <{ ¬ b1' }>
end
| <{ b1 && b2 }> ⇒
match (fold_constants_bexp b1,
fold_constants_bexp b2) with
| (<{true}>, <{true}>) ⇒ <{true}>
| (<{true}>, <{false}>) ⇒ <{false}>
| (<{false}>, <{true}>) ⇒ <{false}>
| (<{false}>, <{false}>) ⇒ <{false}>
| (b1', b2') ⇒ <{ b1' && b2' }>
end
end.
Example fold_bexp_ex1 :
fold_constants_bexp <{ true && ¬(false && true) }>
= <{ true }>.
Proof. reflexivity. Qed.
Example fold_bexp_ex2 :
fold_constants_bexp <{ (X = Y) && (0 = (2 - (1 + 1))) }>
= <{ (X = Y) && true }>.
Proof. reflexivity. Qed.
To fold constants in a command, we apply the appropriate folding
functions on all embedded expressions.
Fixpoint fold_constants_com (c : com) : com :=
match c with
| <{ skip }> ⇒
<{ skip }>
| <{ x := a }> ⇒
<{ x := (fold_constants_aexp a) }>
| <{ c1 ; c2 }> ⇒
<{ fold_constants_com c1 ; fold_constants_com c2 }>
| <{ if b then c1 else c2 end }> ⇒
match fold_constants_bexp b with
| <{true}> ⇒ fold_constants_com c1
| <{false}> ⇒ fold_constants_com c2
| b' ⇒ <{ if b' then fold_constants_com c1
else fold_constants_com c2 end}>
end
| <{ while b do c1 end }> ⇒
match fold_constants_bexp b with
| <{true}> ⇒ <{ while true do skip end }>
| <{false}> ⇒ <{ skip }>
| b' ⇒ <{ while b' do (fold_constants_com c1) end }>
end
end.
Example fold_com_ex1 :
fold_constants_com
(* Original program: *)
<{ X := 4 + 5;
Y := X - 3;
if ((X - Y) = (2 + 4)) then skip
else Y := 0 end;
if (0 ≤ (4 - (2 + 1))) then Y := 0
else skip end;
while (Y = 0) do
X := X + 1
end }>
= (* After constant folding: *)
<{ X := 9;
Y := X - 3;
if ((X - Y) = 6) then skip
else Y := 0 end;
Y := 0;
while (Y = 0) do
X := X + 1
end }>.
match c with
| <{ skip }> ⇒
<{ skip }>
| <{ x := a }> ⇒
<{ x := (fold_constants_aexp a) }>
| <{ c1 ; c2 }> ⇒
<{ fold_constants_com c1 ; fold_constants_com c2 }>
| <{ if b then c1 else c2 end }> ⇒
match fold_constants_bexp b with
| <{true}> ⇒ fold_constants_com c1
| <{false}> ⇒ fold_constants_com c2
| b' ⇒ <{ if b' then fold_constants_com c1
else fold_constants_com c2 end}>
end
| <{ while b do c1 end }> ⇒
match fold_constants_bexp b with
| <{true}> ⇒ <{ while true do skip end }>
| <{false}> ⇒ <{ skip }>
| b' ⇒ <{ while b' do (fold_constants_com c1) end }>
end
end.
Example fold_com_ex1 :
fold_constants_com
(* Original program: *)
<{ X := 4 + 5;
Y := X - 3;
if ((X - Y) = (2 + 4)) then skip
else Y := 0 end;
if (0 ≤ (4 - (2 + 1))) then Y := 0
else skip end;
while (Y = 0) do
X := X + 1
end }>
= (* After constant folding: *)
<{ X := 9;
Y := X - 3;
if ((X - Y) = 6) then skip
else Y := 0 end;
Y := 0;
while (Y = 0) do
X := X + 1
end }>.
Proof. reflexivity. Qed.
Soundness of Constant Folding
Theorem fold_constants_aexp_sound :
atrans_sound fold_constants_aexp.
atrans_sound fold_constants_aexp.
Proof.
unfold atrans_sound. intros a. unfold aequiv. intros st.
induction a; simpl;
(* ANum and AId follow immediately *)
try reflexivity;
(* APlus, AMinus, and AMult follow from the IH
and the observation that
aeval st (<{ a1 + a2 }>)
= ANum ((aeval st a1) + (aeval st a2))
= aeval st (ANum ((aeval st a1) + (aeval st a2)))
(and similarly for AMinus/minus and AMult/mult) *)
try (destruct (fold_constants_aexp a1);
destruct (fold_constants_aexp a2);
rewrite IHa1; rewrite IHa2; reflexivity). Qed.
unfold atrans_sound. intros a. unfold aequiv. intros st.
induction a; simpl;
(* ANum and AId follow immediately *)
try reflexivity;
(* APlus, AMinus, and AMult follow from the IH
and the observation that
aeval st (<{ a1 + a2 }>)
= ANum ((aeval st a1) + (aeval st a2))
= aeval st (ANum ((aeval st a1) + (aeval st a2)))
(and similarly for AMinus/minus and AMult/mult) *)
try (destruct (fold_constants_aexp a1);
destruct (fold_constants_aexp a2);
rewrite IHa1; rewrite IHa2; reflexivity). Qed.
Exercise: 3 stars, standard, optional (fold_bexp_Eq_informal)
Here is an informal proof of the BEq case of the soundness argument for boolean expression constant folding. Read it carefully and compare it to the formal proof that follows. Then fill in the BLe case of the formal proof (without looking at the BEq case, if possible).beval st <{ a1 = a2 }>
= beval st (fold_constants_bexp <{ a1 = a2 }>). There are two cases to consider:
- First, suppose fold_constants_aexp a1 = ANum n1 and
fold_constants_aexp a2 = ANum n2 for some n1 and n2.
fold_constants_bexp <{ a1 = a2 }>
= if n1 =? n2 then <{true}> else <{false}> and
beval st <{a1 = a2}>
= (aeval st a1) =? (aeval st a2). By the soundness of constant folding for arithmetic expressions (Lemma fold_constants_aexp_sound), we know
aeval st a1
= aeval st (fold_constants_aexp a1)
= aeval st (ANum n1)
= n1 and
aeval st a2
= aeval st (fold_constants_aexp a2)
= aeval st (ANum n2)
= n2, so
beval st <{a1 = a2}>
= (aeval a1) =? (aeval a2)
= n1 =? n2. Also, it is easy to see (by considering the cases n1 = n2 and n1 ≠ n2 separately) that
beval st (if n1 =? n2 then <{true}> else <{false}>)
= if n1 =? n2 then beval st <{true}> else beval st <{false}>
= if n1 =? n2 then true else false
= n1 =? n2. So
beval st (<{ a1 = a2 }>)
= n1 =? n2.
= beval st (if n1 =? n2 then <{true}> else <{false}>), as required. - Otherwise, one of fold_constants_aexp a1 and
fold_constants_aexp a2 is not a constant. In this case, we
must show
beval st <{a1 = a2}>
= beval st (<{ (fold_constants_aexp a1) =
(fold_constants_aexp a2) }>), which, by the definition of beval, is the same as showing
(aeval st a1) =? (aeval st a2)
= (aeval st (fold_constants_aexp a1)) =?
(aeval st (fold_constants_aexp a2)). But the soundness of constant folding for arithmetic expressions (fold_constants_aexp_sound) gives us
aeval st a1 = aeval st (fold_constants_aexp a1)
aeval st a2 = aeval st (fold_constants_aexp a2), completing the case. ☐
Theorem fold_constants_bexp_sound:
btrans_sound fold_constants_bexp.
Proof.
unfold btrans_sound. intros b. unfold bequiv. intros st.
induction b;
(* true and false are immediate *)
try reflexivity.
- (* BEq *)
simpl.
remember (fold_constants_aexp a1) as a1' eqn:Heqa1'.
remember (fold_constants_aexp a2) as a2' eqn:Heqa2'.
replace (aeval st a1) with (aeval st a1') by
(subst a1'; rewrite <- fold_constants_aexp_sound; reflexivity).
replace (aeval st a2) with (aeval st a2') by
(subst a2'; rewrite <- fold_constants_aexp_sound; reflexivity).
destruct a1'; destruct a2'; try reflexivity.
(* The only interesting case is when both a1 and a2
become constants after folding *)
simpl. destruct (n =? n0); reflexivity.
- (* BNeq *)
simpl.
remember (fold_constants_aexp a1) as a1' eqn:Heqa1'.
remember (fold_constants_aexp a2) as a2' eqn:Heqa2'.
replace (aeval st a1) with (aeval st a1') by
(subst a1'; rewrite <- fold_constants_aexp_sound; reflexivity).
replace (aeval st a2) with (aeval st a2') by
(subst a2'; rewrite <- fold_constants_aexp_sound; reflexivity).
destruct a1'; destruct a2'; try reflexivity.
(* The only interesting case is when both a1 and a2
become constants after folding *)
simpl. destruct (n =? n0); reflexivity.
- (* BLe *)
(* FILL IN HERE *) admit.
- (* BNot *)
simpl. remember (fold_constants_bexp b) as b' eqn:Heqb'.
rewrite IHb.
destruct b'; reflexivity.
- (* BAnd *)
simpl.
remember (fold_constants_bexp b1) as b1' eqn:Heqb1'.
remember (fold_constants_bexp b2) as b2' eqn:Heqb2'.
rewrite IHb1. rewrite IHb2.
destruct b1'; destruct b2'; reflexivity.
(* FILL IN HERE *) Admitted.
☐
btrans_sound fold_constants_bexp.
Proof.
unfold btrans_sound. intros b. unfold bequiv. intros st.
induction b;
(* true and false are immediate *)
try reflexivity.
- (* BEq *)
simpl.
remember (fold_constants_aexp a1) as a1' eqn:Heqa1'.
remember (fold_constants_aexp a2) as a2' eqn:Heqa2'.
replace (aeval st a1) with (aeval st a1') by
(subst a1'; rewrite <- fold_constants_aexp_sound; reflexivity).
replace (aeval st a2) with (aeval st a2') by
(subst a2'; rewrite <- fold_constants_aexp_sound; reflexivity).
destruct a1'; destruct a2'; try reflexivity.
(* The only interesting case is when both a1 and a2
become constants after folding *)
simpl. destruct (n =? n0); reflexivity.
- (* BNeq *)
simpl.
remember (fold_constants_aexp a1) as a1' eqn:Heqa1'.
remember (fold_constants_aexp a2) as a2' eqn:Heqa2'.
replace (aeval st a1) with (aeval st a1') by
(subst a1'; rewrite <- fold_constants_aexp_sound; reflexivity).
replace (aeval st a2) with (aeval st a2') by
(subst a2'; rewrite <- fold_constants_aexp_sound; reflexivity).
destruct a1'; destruct a2'; try reflexivity.
(* The only interesting case is when both a1 and a2
become constants after folding *)
simpl. destruct (n =? n0); reflexivity.
- (* BLe *)
(* FILL IN HERE *) admit.
- (* BNot *)
simpl. remember (fold_constants_bexp b) as b' eqn:Heqb'.
rewrite IHb.
destruct b'; reflexivity.
- (* BAnd *)
simpl.
remember (fold_constants_bexp b1) as b1' eqn:Heqb1'.
remember (fold_constants_bexp b2) as b2' eqn:Heqb2'.
rewrite IHb1. rewrite IHb2.
destruct b1'; destruct b2'; reflexivity.
(* FILL IN HERE *) Admitted.
☐
Exercise: 3 stars, standard (fold_constants_com_sound)
Complete the while case of the following proof.
Theorem fold_constants_com_sound :
ctrans_sound fold_constants_com.
Proof.
unfold ctrans_sound. intros c.
induction c; simpl.
- (* skip *) apply refl_cequiv.
- (* := *) apply CAsgn_congruence.
apply fold_constants_aexp_sound.
- (* ; *) apply CSeq_congruence; assumption.
- (* if *)
assert (bequiv b (fold_constants_bexp b)). {
apply fold_constants_bexp_sound. }
destruct (fold_constants_bexp b) eqn:Heqb;
try (apply CIf_congruence; assumption).
(* (If the optimization doesn't eliminate the if, then the
result is easy to prove from the IH and
fold_constants_bexp_sound.) *)
+ (* b always true *)
apply trans_cequiv with c1; try assumption.
apply if_true; assumption.
+ (* b always false *)
apply trans_cequiv with c2; try assumption.
apply if_false; assumption.
- (* while *)
(* FILL IN HERE *) Admitted.
☐
ctrans_sound fold_constants_com.
Proof.
unfold ctrans_sound. intros c.
induction c; simpl.
- (* skip *) apply refl_cequiv.
- (* := *) apply CAsgn_congruence.
apply fold_constants_aexp_sound.
- (* ; *) apply CSeq_congruence; assumption.
- (* if *)
assert (bequiv b (fold_constants_bexp b)). {
apply fold_constants_bexp_sound. }
destruct (fold_constants_bexp b) eqn:Heqb;
try (apply CIf_congruence; assumption).
(* (If the optimization doesn't eliminate the if, then the
result is easy to prove from the IH and
fold_constants_bexp_sound.) *)
+ (* b always true *)
apply trans_cequiv with c1; try assumption.
apply if_true; assumption.
+ (* b always false *)
apply trans_cequiv with c2; try assumption.
apply if_false; assumption.
- (* while *)
(* FILL IN HERE *) Admitted.
☐
Soundness of (0 + n) Elimination, Redux
Exercise: 4 stars, standard, optional (optimize_0plus_var)
Recall the definition optimize_0plus from the Imp chapter of Logical Foundations:Fixpoint optimize_0plus (a:aexp) : aexp :=
match a with
| ANum n ⇒
ANum n
| <{ 0 + a2 }> ⇒
optimize_0plus a2
| <{ a1 + a2 }> ⇒
<{ (optimize_0plus a1) + (optimize_0plus a2) }>
| <{ a1 - a2 }> ⇒
<{ (optimize_0plus a1) - (optimize_0plus a2) }>
| <{ a1 × a2 }> ⇒
<{ (optimize_0plus a1) × (optimize_0plus a2) }>
end. Note that this function is defined over the old version of aexps, without states.
optimize_0plus_aexp
optimize_0plus_bexp
optimize_0plus_com
Fixpoint optimize_0plus_aexp (a : aexp) : aexp
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Fixpoint optimize_0plus_bexp (b : bexp) : bexp
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Fixpoint optimize_0plus_com (c : com) : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_optimize_0plus:
optimize_0plus_com
<{ while X ≠ 0 do X := 0 + X - 1 end }>
= <{ while X ≠ 0 do X := X - 1 end }>.
Proof.
(* FILL IN HERE *) Admitted.
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Fixpoint optimize_0plus_bexp (b : bexp) : bexp
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Fixpoint optimize_0plus_com (c : com) : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_optimize_0plus:
optimize_0plus_com
<{ while X ≠ 0 do X := 0 + X - 1 end }>
= <{ while X ≠ 0 do X := X - 1 end }>.
Proof.
(* FILL IN HERE *) Admitted.
Prove that these three functions are sound, as we did for
fold_constants_×. Make sure you use the congruence lemmas in the
proof of optimize_0plus_com -- otherwise it will be long!
Theorem optimize_0plus_aexp_sound:
atrans_sound optimize_0plus_aexp.
Proof.
(* FILL IN HERE *) Admitted.
Theorem optimize_0plus_bexp_sound :
btrans_sound optimize_0plus_bexp.
Proof.
(* FILL IN HERE *) Admitted.
Theorem optimize_0plus_com_sound :
ctrans_sound optimize_0plus_com.
Proof.
(* FILL IN HERE *) Admitted.
atrans_sound optimize_0plus_aexp.
Proof.
(* FILL IN HERE *) Admitted.
Theorem optimize_0plus_bexp_sound :
btrans_sound optimize_0plus_bexp.
Proof.
(* FILL IN HERE *) Admitted.
Theorem optimize_0plus_com_sound :
ctrans_sound optimize_0plus_com.
Proof.
(* FILL IN HERE *) Admitted.
Finally, let's define a compound optimizer on commands that first
folds constants (using fold_constants_com) and then eliminates
0 + n terms (using optimize_0plus_com).
Prove that this optimizer is sound.
Proving Inequivalence
X := a1; Y := a2 and c2 is the command
X := a1; Y := a2' where a2' is formed by substituting a1 for all occurrences of X in a2.
c1 = (X := 42 + 53;
Y := Y + X)
c2 = (X := 42 + 53;
Y := Y + (42 + 53)) Clearly, this particular c1 and c2 are equivalent. Is this true in general?
Fixpoint subst_aexp (x : string) (u : aexp) (a : aexp) : aexp :=
match a with
| ANum n ⇒
ANum n
| AId x' ⇒
if String.eqb x x' then u else AId x'
| <{ a1 + a2 }> ⇒
<{ (subst_aexp x u a1) + (subst_aexp x u a2) }>
| <{ a1 - a2 }> ⇒
<{ (subst_aexp x u a1) - (subst_aexp x u a2) }>
| <{ a1 × a2 }> ⇒
<{ (subst_aexp x u a1) × (subst_aexp x u a2) }>
end.
Example subst_aexp_ex :
subst_aexp X <{42 + 53}> <{Y + X}>
= <{ Y + (42 + 53)}>.
match a with
| ANum n ⇒
ANum n
| AId x' ⇒
if String.eqb x x' then u else AId x'
| <{ a1 + a2 }> ⇒
<{ (subst_aexp x u a1) + (subst_aexp x u a2) }>
| <{ a1 - a2 }> ⇒
<{ (subst_aexp x u a1) - (subst_aexp x u a2) }>
| <{ a1 × a2 }> ⇒
<{ (subst_aexp x u a1) × (subst_aexp x u a2) }>
end.
Example subst_aexp_ex :
subst_aexp X <{42 + 53}> <{Y + X}>
= <{ Y + (42 + 53)}>.
Proof. simpl. reflexivity. Qed.
And here is the property we are interested in, expressing the
claim that commands c1 and c2 as described above are
always equivalent.
Definition subst_equiv_property : Prop := ∀ x1 x2 a1 a2,
cequiv <{ x1 := a1; x2 := a2 }>
<{ x1 := a1; x2 := subst_aexp x1 a1 a2 }>.
cequiv <{ x1 := a1; x2 := a2 }>
<{ x1 := a1; x2 := subst_aexp x1 a1 a2 }>.
Sadly, the property does not always hold.
Here is a counterexample:
X := X + 1; Y := X If we perform the substitution, we get
X := X + 1; Y := X + 1 which clearly isn't equivalent.
X := X + 1; Y := X If we perform the substitution, we get
X := X + 1; Y := X + 1 which clearly isn't equivalent.
Theorem subst_inequiv :
¬ subst_equiv_property.
¬ subst_equiv_property.
Proof.
unfold subst_equiv_property.
intros Contra.
(* Here is the counterexample: assuming that subst_equiv_property
holds allows us to prove that these two programs are
equivalent... *)
remember <{ X := X + 1;
Y := X }>
as c1.
remember <{ X := X + 1;
Y := X + 1 }>
as c2.
assert (cequiv c1 c2) by (subst; apply Contra).
clear Contra.
(* ... allows us to show that the command c2 can terminate
in two different final states:
st1 = (Y !-> 1 ; X !-> 1)
st2 = (Y !-> 2 ; X !-> 1). *)
remember (Y !-> 1 ; X !-> 1) as st1.
remember (Y !-> 2 ; X !-> 1) as st2.
assert (H1 : empty_st =[ c1 ]=> st1);
assert (H2 : empty_st =[ c2 ]=> st2);
try (subst;
apply E_Seq with (st' := (X !-> 1));
apply E_Asgn; reflexivity).
clear Heqc1 Heqc2.
apply H in H1.
clear H.
(* Finally, we use the fact that evaluation is deterministic
to obtain a contradiction. *)
assert (Hcontra : st1 = st2)
by (apply (ceval_deterministic c2 empty_st); assumption).
clear H1 H2.
assert (Hcontra' : st1 Y = st2 Y)
by (rewrite Hcontra; reflexivity).
subst. discriminate. Qed.
unfold subst_equiv_property.
intros Contra.
(* Here is the counterexample: assuming that subst_equiv_property
holds allows us to prove that these two programs are
equivalent... *)
remember <{ X := X + 1;
Y := X }>
as c1.
remember <{ X := X + 1;
Y := X + 1 }>
as c2.
assert (cequiv c1 c2) by (subst; apply Contra).
clear Contra.
(* ... allows us to show that the command c2 can terminate
in two different final states:
st1 = (Y !-> 1 ; X !-> 1)
st2 = (Y !-> 2 ; X !-> 1). *)
remember (Y !-> 1 ; X !-> 1) as st1.
remember (Y !-> 2 ; X !-> 1) as st2.
assert (H1 : empty_st =[ c1 ]=> st1);
assert (H2 : empty_st =[ c2 ]=> st2);
try (subst;
apply E_Seq with (st' := (X !-> 1));
apply E_Asgn; reflexivity).
clear Heqc1 Heqc2.
apply H in H1.
clear H.
(* Finally, we use the fact that evaluation is deterministic
to obtain a contradiction. *)
assert (Hcontra : st1 = st2)
by (apply (ceval_deterministic c2 empty_st); assumption).
clear H1 H2.
assert (Hcontra' : st1 Y = st2 Y)
by (rewrite Hcontra; reflexivity).
subst. discriminate. Qed.
Exercise: 4 stars, standard, optional (better_subst_equiv)
The equivalence we had in mind above was not complete nonsense -- in fact, it was actually almost right. To make it correct, we just need to exclude the case where the variable X occurs in the right-hand side of the first assignment statement.
Inductive var_not_used_in_aexp (x : string) : aexp → Prop :=
| VNUNum : ∀ n, var_not_used_in_aexp x (ANum n)
| VNUId : ∀ y, x ≠ y → var_not_used_in_aexp x (AId y)
| VNUPlus : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 + a2 }>)
| VNUMinus : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 - a2 }>)
| VNUMult : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 × a2 }>).
Lemma aeval_weakening : ∀ x st a ni,
var_not_used_in_aexp x a →
aeval (x !-> ni ; st) a = aeval st a.
Proof.
(* FILL IN HERE *) Admitted.
| VNUNum : ∀ n, var_not_used_in_aexp x (ANum n)
| VNUId : ∀ y, x ≠ y → var_not_used_in_aexp x (AId y)
| VNUPlus : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 + a2 }>)
| VNUMinus : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 - a2 }>)
| VNUMult : ∀ a1 a2,
var_not_used_in_aexp x a1 →
var_not_used_in_aexp x a2 →
var_not_used_in_aexp x (<{ a1 × a2 }>).
Lemma aeval_weakening : ∀ x st a ni,
var_not_used_in_aexp x a →
aeval (x !-> ni ; st) a = aeval st a.
Proof.
(* FILL IN HERE *) Admitted.
Using var_not_used_in_aexp, formalize and prove a correct version
of subst_equiv_property.
(* FILL IN HERE *)
☐
☐
Exercise: 3 stars, standard (inequiv_exercise)
Prove that an infinite loop is not equivalent to skip
Theorem inequiv_exercise:
¬ cequiv <{ while true do skip end }> <{ skip }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
¬ cequiv <{ while true do skip end }> <{ skip }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Extended Exercise: Nondeterministic Imp
x = 0;
f(++x, x) might call f with arguments (1, 0) or (1, 1), depending how the compiler chooses to order things. This can be a little confusing for programmers, but it gives the compiler writer useful freedom.
HAVOC Y;
Z := Y × 2 the value of Y can be any number, while the value of Z is twice that of Y (so Z is always even). Note that we are not saying anything about the probabilities of the outcomes -- just that there are (infinitely) many different outcomes that can possibly happen after executing this nondeterministic code.
To formalize Himp, we first add a clause to the definition of
commands.
Inductive com : Type :=
| CSkip : com
| CAsgn : string → aexp → com
| CSeq : com → com → com
| CIf : bexp → com → com → com
| CWhile : bexp → com → com
| CHavoc : string → com. (* <--- NEW *)
Notation "'havoc' l" := (CHavoc l)
(in custom com at level 60, l constr at level 0).
Notation "'skip'" :=
CSkip (in custom com at level 0).
Notation "x := y" :=
(CAsgn x y)
(in custom com at level 0, x constr at level 0,
y at level 85, no associativity).
Notation "x ; y" :=
(CSeq x y)
(in custom com at level 90, right associativity).
Notation "'if' x 'then' y 'else' z 'end'" :=
(CIf x y z)
(in custom com at level 89, x at level 99,
y at level 99, z at level 99).
Notation "'while' x 'do' y 'end'" :=
(CWhile x y)
(in custom com at level 89, x at level 99, y at level 99).
| CSkip : com
| CAsgn : string → aexp → com
| CSeq : com → com → com
| CIf : bexp → com → com → com
| CWhile : bexp → com → com
| CHavoc : string → com. (* <--- NEW *)
Notation "'havoc' l" := (CHavoc l)
(in custom com at level 60, l constr at level 0).
Notation "'skip'" :=
CSkip (in custom com at level 0).
Notation "x := y" :=
(CAsgn x y)
(in custom com at level 0, x constr at level 0,
y at level 85, no associativity).
Notation "x ; y" :=
(CSeq x y)
(in custom com at level 90, right associativity).
Notation "'if' x 'then' y 'else' z 'end'" :=
(CIf x y z)
(in custom com at level 89, x at level 99,
y at level 99, z at level 99).
Notation "'while' x 'do' y 'end'" :=
(CWhile x y)
(in custom com at level 89, x at level 99, y at level 99).
Exercise: 2 stars, standard (himp_ceval)
Now, we must extend the operational semantics. We have provided a template for the ceval relation below, specifying the big-step semantics. What rule(s) must be added to the definition of ceval to formalize the behavior of the HAVOC command?
Reserved Notation "st '=[' c ']=>' st'"
(at level 40, c custom com at level 99, st constr,
st' constr at next level).
Inductive ceval : com → state → state → Prop :=
| E_Skip : ∀ st,
st =[ skip ]=> st
| E_Asgn : ∀ st a n x,
aeval st a = n →
st =[ x := a ]=> (x !-> n ; st)
| E_Seq : ∀ c1 c2 st st' st'',
st =[ c1 ]=> st' →
st' =[ c2 ]=> st'' →
st =[ c1 ; c2 ]=> st''
| E_IfTrue : ∀ st st' b c1 c2,
beval st b = true →
st =[ c1 ]=> st' →
st =[ if b then c1 else c2 end ]=> st'
| E_IfFalse : ∀ st st' b c1 c2,
beval st b = false →
st =[ c2 ]=> st' →
st =[ if b then c1 else c2 end ]=> st'
| E_WhileFalse : ∀ b st c,
beval st b = false →
st =[ while b do c end ]=> st
| E_WhileTrue : ∀ st st' st'' b c,
beval st b = true →
st =[ c ]=> st' →
st' =[ while b do c end ]=> st'' →
st =[ while b do c end ]=> st''
(* FILL IN HERE *)
where "st =[ c ]=> st'" := (ceval c st st').
(at level 40, c custom com at level 99, st constr,
st' constr at next level).
Inductive ceval : com → state → state → Prop :=
| E_Skip : ∀ st,
st =[ skip ]=> st
| E_Asgn : ∀ st a n x,
aeval st a = n →
st =[ x := a ]=> (x !-> n ; st)
| E_Seq : ∀ c1 c2 st st' st'',
st =[ c1 ]=> st' →
st' =[ c2 ]=> st'' →
st =[ c1 ; c2 ]=> st''
| E_IfTrue : ∀ st st' b c1 c2,
beval st b = true →
st =[ c1 ]=> st' →
st =[ if b then c1 else c2 end ]=> st'
| E_IfFalse : ∀ st st' b c1 c2,
beval st b = false →
st =[ c2 ]=> st' →
st =[ if b then c1 else c2 end ]=> st'
| E_WhileFalse : ∀ b st c,
beval st b = false →
st =[ while b do c end ]=> st
| E_WhileTrue : ∀ st st' st'' b c,
beval st b = true →
st =[ c ]=> st' →
st' =[ while b do c end ]=> st'' →
st =[ while b do c end ]=> st''
(* FILL IN HERE *)
where "st =[ c ]=> st'" := (ceval c st st').
As a sanity check, the following claims should be provable for
your definition:
Example havoc_example1 : empty_st =[ havoc X ]=> (X !-> 0).
Proof.
(* FILL IN HERE *) Admitted.
Example havoc_example2 :
empty_st =[ skip; havoc Z ]=> (Z !-> 42).
Proof.
(* FILL IN HERE *) Admitted.
(* Do not modify the following line: *)
Definition manual_grade_for_Check_rule_for_HAVOC : option (nat×string) := None.
☐
Proof.
(* FILL IN HERE *) Admitted.
Example havoc_example2 :
empty_st =[ skip; havoc Z ]=> (Z !-> 42).
Proof.
(* FILL IN HERE *) Admitted.
(* Do not modify the following line: *)
Definition manual_grade_for_Check_rule_for_HAVOC : option (nat×string) := None.
☐
Let's apply this definition to prove some nondeterministic
programs equivalent / inequivalent.
Exercise: 3 stars, standard (havoc_swap)
Are the following two programs equivalent?
If you think they are equivalent, prove it. If you think they are
not, prove that.
Theorem pXY_cequiv_pYX :
cequiv pXY pYX ∨ ¬cequiv pXY pYX.
Proof.
(* Hint: You may want to use t_update_permute at some point,
in which case you'll probably be left with X ≠ Y as a
hypothesis. You can use discriminate to discharge this. *)
(* FILL IN HERE *) Admitted.
☐
cequiv pXY pYX ∨ ¬cequiv pXY pYX.
Proof.
(* Hint: You may want to use t_update_permute at some point,
in which case you'll probably be left with X ≠ Y as a
hypothesis. You can use discriminate to discharge this. *)
(* FILL IN HERE *) Admitted.
☐
If you think they are equivalent, then prove it. If you think they
are not, then prove that. (Hint: You may find the assert tactic
useful.)
Theorem ptwice_cequiv_pcopy :
cequiv ptwice pcopy ∨ ¬cequiv ptwice pcopy.
Proof. (* FILL IN HERE *) Admitted.
☐
cequiv ptwice pcopy ∨ ¬cequiv ptwice pcopy.
Proof. (* FILL IN HERE *) Admitted.
☐
Exercise: 4 stars, advanced (p1_p2_term)
Consider the following commands:
Definition p1 : com :=
<{ while ¬ (X = 0) do
havoc Y;
X := X + 1
end }>.
Definition p2 : com :=
<{ while ¬ (X = 0) do
skip
end }>.
<{ while ¬ (X = 0) do
havoc Y;
X := X + 1
end }>.
Definition p2 : com :=
<{ while ¬ (X = 0) do
skip
end }>.
Intuitively, p1 and p2 have the same termination behavior:
either they loop forever, or they terminate in the same state they
started in. We can capture the termination behavior of p1 and
p2 individually with these lemmas:
Lemma p1_may_diverge : ∀ st st', st X ≠ 0 →
¬ st =[ p1 ]=> st'.
Proof. (* FILL IN HERE *) Admitted.
Lemma p2_may_diverge : ∀ st st', st X ≠ 0 →
¬ st =[ p2 ]=> st'.
Proof.
(* FILL IN HERE *) Admitted.
☐
¬ st =[ p1 ]=> st'.
Proof. (* FILL IN HERE *) Admitted.
Lemma p2_may_diverge : ∀ st st', st X ≠ 0 →
¬ st =[ p2 ]=> st'.
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 4 stars, advanced (p1_p2_equiv)
Use these two lemmas to prove that p1 and p2 are actually equivalent.Exercise: 4 stars, advanced (p3_p4_inequiv)
Prove that the following programs are not equivalent. (Hint: What should the value of Z be when p3 terminates? What about p4?)
Definition p3 : com :=
<{ Z := 1;
while X ≠ 0 do
havoc X;
havoc Z
end }>.
Definition p4 : com :=
<{ X := 0;
Z := 1 }>.
Theorem p3_p4_inequiv : ¬ cequiv p3 p4.
Proof. (* FILL IN HERE *) Admitted.
☐
<{ Z := 1;
while X ≠ 0 do
havoc X;
havoc Z
end }>.
Definition p4 : com :=
<{ X := 0;
Z := 1 }>.
Theorem p3_p4_inequiv : ¬ cequiv p3 p4.
Proof. (* FILL IN HERE *) Admitted.
☐
Exercise: 5 stars, advanced, optional (p5_p6_equiv)
Prove that the following commands are equivalent. (Hint: As mentioned above, our definition of cequiv for Himp only takes into account the sets of possible terminating configurations: two programs are equivalent if and only if the set of possible terminating states is the same for both programs when given a same starting state st. If p5 terminates, what should the final state be? Conversely, is it always possible to make p5 terminate?)
Definition p5 : com :=
<{ while X ≠ 1 do
havoc X
end }>.
Definition p6 : com :=
<{ X := 1 }>.
Theorem p5_p6_equiv : cequiv p5 p6.
Proof. (* FILL IN HERE *) Admitted.
☐
<{ while X ≠ 1 do
havoc X
end }>.
Definition p6 : com :=
<{ X := 1 }>.
Theorem p5_p6_equiv : cequiv p5 p6.
Proof. (* FILL IN HERE *) Admitted.
☐
Additional Exercises
Exercise: 3 stars, standard, optional (swap_noninterfering_assignments)
(Hint: You'll need functional_extensionality for this one.)
Theorem swap_noninterfering_assignments: ∀ l1 l2 a1 a2,
l1 ≠ l2 →
var_not_used_in_aexp l1 a2 →
var_not_used_in_aexp l2 a1 →
cequiv
<{ l1 := a1; l2 := a2 }>
<{ l2 := a2; l1 := a1 }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
l1 ≠ l2 →
var_not_used_in_aexp l1 a2 →
var_not_used_in_aexp l2 a1 →
cequiv
<{ l1 := a1; l2 := a2 }>
<{ l2 := a2; l1 := a1 }>.
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 4 stars, standard, optional (for_while_equiv)
This exercise extends the optional add_for_loop exercise from the Imp chapter, where you were asked to extend the language of commands with C-style for loops. Prove that the command:for (c1; b; c2) {
c3
} is equivalent to:
c1;
while b do
c3;
c2
end
(* FILL IN HERE *)
☐
☐
Exercise: 4 stars, advanced, optional (capprox)
In this exercise we define an asymmetric variant of program equivalence we call program approximation. We say that a program c1 approximates a program c2 when, for each of the initial states for which c1 terminates, c2 also terminates and produces the same final state. Formally, program approximation is defined as follows:
For example, the program
c1 = while X ≠ 1 do
X := X - 1
end approximates c2 = X := 1, but c2 does not approximate c1 since c1 does not terminate when X = 0 but c2 does. If two programs approximate each other in both directions, then they are equivalent.
Find two programs c3 and c4 such that neither approximates
the other.
c1 = while X ≠ 1 do
X := X - 1
end approximates c2 = X := 1, but c2 does not approximate c1 since c1 does not terminate when X = 0 but c2 does. If two programs approximate each other in both directions, then they are equivalent.
Definition c3 : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Definition c4 : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem c3_c4_different : ¬ capprox c3 c4 ∧ ¬ capprox c4 c3.
Proof. (* FILL IN HERE *) Admitted.
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Definition c4 : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem c3_c4_different : ¬ capprox c3 c4 ∧ ¬ capprox c4 c3.
Proof. (* FILL IN HERE *) Admitted.
Find a program cmin that approximates every other program.
Definition cmin : com
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem cmin_minimal : ∀ c, capprox cmin c.
Proof. (* FILL IN HERE *) Admitted.
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem cmin_minimal : ∀ c, capprox cmin c.
Proof. (* FILL IN HERE *) Admitted.
Finally, find a non-trivial property which is preserved by
program approximation (when going from left to right).
Definition zprop (c : com) : Prop
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem zprop_preserving : ∀ c c',
zprop c → capprox c c' → zprop c'.
Proof. (* FILL IN HERE *) Admitted.
☐
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Theorem zprop_preserving : ∀ c c',
zprop c → capprox c c' → zprop c'.
Proof. (* FILL IN HERE *) Admitted.
☐
(* 2021-11-26 13:27 *)